Tissue microarray analysis of RANKL in cutaneous lupus erythematosus and psoriasis - Toberer, Ferdinand; Sykora, Jaromir; Göttel, Daniel; Ruland, Vincent; Hartschuh, Wolfgang; Enk, Alexander; Luger, Thomas A.; Beissert, Stefan; Loser, Karin; Joos, Stefan; Krammer, Peter H.; Kuhn, Annegret (Experimental dermatology, 2011)
Abstract: Recently, it was discovered that the receptor activator of nuclear factor κB (RANK)/RANK ligand (RANKL) is part of an important signal transduction pathway for tissue homoeostasis. Therefore, we were interested in investigating RANKL expression in the epidermis of skin lesions from patients with different subtypes of cutaneous lupus erythematosus (CLE) and psoriasis as well as normal healthy donors. Using the tissue microarray technique, skin biopsy specimens were evaluated by immunohistochemistry. RANKL showed a significantly increased expression in the epidermis of skin biopsy specimens from patients with psoriasis (median: 4, range: 0-5) compared to patients with CLE (median: 0, range: 0-4) (P < 0.001). No significant differences in epidermal RANKL expression between the CLE subtypes were detected. These data show a different expression of RANKL in the epidermis of skin lesions from patients with CLE compared to those with psoriasis suggesting that RANKL might play an important role in the pathogenesis of the disease.